Dietary intake in children on the autism spectrum is altered and linked to differences in autistic traits and sensory processing styles. Issue 10 (26th August 2022) - Mathew, Nisha E.; Mallitt, Kylie‐Ann; Masi, Anne; Katz, Tamarah; Walker, Adam K.; Morris, Margaret J.; Ooi, Chee Y.
Abstract: Diets of children and adolescents on the autism spectrum often differ when compared to their non‐autistic peers. Most dietary studies have been limited by small sample sizes and rarely assess the heterogeneity of autism. Addressing this gap, this study compared the anthropometrics, dietary composition, dietary quality, and food variety of 154 Australian children and adolescents on the spectrum and 213 non‐autistic children (71 siblings and 142 unrelated controls). Beyond the case‐control approach, within‐group comparisons assessed the influence of autism clinical presentations and sensory processing styles on body mass index (BMI) and measures of dietary intake among those on the spectrum. In this word first study of diet that included between‐group comparisons with non‐autistic peers (siblings and an unrelated comparison group) and within‐autism group comparisons, we found that children on the spectrum consumed limited variety and lower quality of food and non‐autistic siblings also ate comparably higher levels of energy‐dense, nutrient poor food, and less diary. This may be due to autistic traits influencing family's diets or shared sensory sensitivities driving dietary intake. Within the autism group, higher autistic traits were associated with lower BMIs and a specific dietary pattern higher in simple carbohydrates and lower in unprocessed protein. Contrastingly, greater sensitivity to sensory stimuli was associated with a healthier diet. Increased age was linked to more varied diets but also diets higher in saturated fats and energy‐dense, nutrient poor foods. Overall, this research highlights that potential mediators of dietary intake, such as familial influences, autistic traits, sensory processing styles, age and sex, need to be considered when assessing diet in the autistic population. Lay Summary: In this study of dietary differences linked to autism, children, and teenagers on the spectrum ate fewer different foods and were less likely to eat recommended amounts of fruits and vegetables when compared to non‐autistic siblings and unrelated children and teenagers. There were also family differences, in that those on the spectrum and their siblings ate more unhealthy foods and less dairy. Among those on the spectrum, dietary differences were linked to age, sex, autistic traits and sensory processing styles.